The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.ophtha.2009.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity Outcomes after Cataract Surgery in Patients with Age-Related Macular Degeneration: Age-Related Eye Disease Study Report No. 27

Abstract: Objective-To evaluate visual acuity outcomes after cataract surgery in patients with varying degrees of age-related macular degeneration (AMD). Design-Cohort study.Participants-A total of 4757 participants enrolled in the Age-Related Eye Disease Study (AREDS), a prospective, multicenter, epidemiological study of the clinical course of cataract and AMD and a randomized controlled trial of antioxidants and minerals.Methods-Standardized lens and fundus photographs, performed at baseline and annual visits, were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 34 publications
5
44
0
3
Order By: Relevance
“…More recently, studies published have not showed an increase in recurrence, number of injections or worsening of visual acuity when compared with non-operated eyes [15,16,[25][26][27][39][40][41][42][43][50][51][52][53][54][55][56]. However, Lee and cols.…”
Section: Neovascular Amdmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, studies published have not showed an increase in recurrence, number of injections or worsening of visual acuity when compared with non-operated eyes [15,16,[25][26][27][39][40][41][42][43][50][51][52][53][54][55][56]. However, Lee and cols.…”
Section: Neovascular Amdmentioning
confidence: 99%
“…The studies published about cataract surgery in patients with neovascular AMD are mainly retrospective, FAG was only performed as a diagnostic test and not on the follow-up; some of them without control group and with short periods of follow-up [15,16,[25][26][27][39][40][41][42][43][50][51][52][53][54][55]58]. In addition, the protocols used in the reported studies, were inhomogeneous (treat and extend, pro-re-nata and monthly injections), but none compared these protocols between them, or even between different anti-VEGF agents (bevacizumab, ranibizumab or aflibercept) [38,39,[41][42][43][52][53][54][55].…”
Section: Neovascular Amdmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] It has been suggested that the 1-day postoperative intraocular pressure (IOP) check post routine uncomplicated phacoemulsification can be abandoned for a number of reasons. 1,[4][5][6][7] Some of these include the fact that new surgical complications are unlikely to be picked up on the first day, peak IOP may have already passed, economical constraints, improved postoperative outcomes and low complication rates.…”
Section: Introductionmentioning
confidence: 99%
“…Large studies have shown that cataract surgery in these patients can provide sustained improvements in visual acuity. 14,15 However, the impact of the procedure on the course of retinal disease remains controversial. Some evidence suggests increases in both the incidence and progression rate of diabetic retinopathy at 1 year after phacoemulsification cataract surgery, and findings are inconsistent from large studies about the association between cataract surgery and long-term risk for the development of either early or late AMD.…”
mentioning
confidence: 99%